2012
DOI: 10.1136/bjophthalmol-2012-302121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of preservative-free latanoprost eyedrops, compared with BAK-preserved latanoprost in patients with ocular hypertension or glaucoma

Abstract: Preservative-free latanoprost has the same efficacy as BPL, with improved local tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 24 publications
10
96
0
4
Order By: Relevance
“…The present study evaluated IOP efficacy data throughout the day compared to the single time point analysis in the phase III study. The data in the present study show the diurnal IOPlowering behavior of the preservative-free formulation, which was similar to that for the preserved formulation, and supported the optimization of the timing for the IOP assessment in the confirmatory phase III study 20 . Since the early morning time point in the present study was shown to be the most challenging time to demonstrate non-inferiority of the preservative-free to the preserved formulation, it was decided to conduct the IOP assessment during that time in the phase III study, this time point being strongly representative of the IOP-lowering effect in the afternoon.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…The present study evaluated IOP efficacy data throughout the day compared to the single time point analysis in the phase III study. The data in the present study show the diurnal IOPlowering behavior of the preservative-free formulation, which was similar to that for the preserved formulation, and supported the optimization of the timing for the IOP assessment in the confirmatory phase III study 20 . Since the early morning time point in the present study was shown to be the most challenging time to demonstrate non-inferiority of the preservative-free to the preserved formulation, it was decided to conduct the IOP assessment during that time in the phase III study, this time point being strongly representative of the IOP-lowering effect in the afternoon.…”
Section: Discussionsupporting
confidence: 60%
“…Despite the small sample size in the present study, this data is aligned with the demonstration of non-inferiority in the pivotal phase III study 20 . In addition, the data from the present study demonstrate excellent diurnal control of IOP by both preservative-free and preserved latanoprost.…”
Section: Preservative-free Versus Preserved Latanoprost Eye Dropssupporting
confidence: 59%
See 3 more Smart Citations